Mammalian microRNA assembly and function - Mourelatos, Zissimos (Henry Stewart Talks, 2007)
miRNAs and RNA interference, nuclear biogenesis and cytoplasmic processing, siRNA biogenesis and assembly, Silencing by target mRNA cleavage and "translational repression", RISC assembly in flies, RISC activity and Dicer, Model of the miRNA assembly pathway in humans, Prediction of miRNA targets, Compensatory mutations: rescue, How miRNAs and siRNAs recognize their targets, Additional principles of target RNA recognition by miRNAs and siRNAs
Reviewed at 2016/10/13